Strategies Towards the New Sustainability Paradigm: Managing the Great Transition to Sustainable Global Democracy - Schwarz-Herion, Odile (Springer, 2015)
On a historical global turning point, this book offers a thorough exploration of the “New Sustainability Paradigm”, originally developed by the Global Scenario Group (GSG) of the Stockholm Environmental Institute (SEI) as a starting point for analyzing real-life transitions and transformations. 11 contributors from 5 continents present detailed analyses of economic and political transitions in Western and Eastern Europe, the USA, the Middle East, and in Asia, discussing the role of different players in the implementation of the New Sustainability Paradigm.